Robust DUT-67 material for highly efficient removal of the Cr(VI) ion from an aqueous solution - Shen, Yanqiong; Yang, Qingsong; Gao, Yongqiang; Qian, Jinjie; Li, Qipeng (Frontiers in Chemistry, 2023)
Robust DUT-67 was synthesized by the hydrothermal method and characterized by powder X-ray diffraction (PXRD), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). To systematically study the removal of Cr(VI) ion by DUT-67, single-factor, competition ion, material regeneration, kinetic, and thermodynamic experiments were designed. The experimental results show that DUT-67 had a maximum removal rate of 96.1% and a maximum adsorption capacity of 105.42 mg g−1 with material regeneration and outstanding selective adsorption. In addition, the process of removal of the Cr(VI) ion from an aqueous solution by DUT-67, which accorded with the pseudo-second-order kinetics model and Langmuir model, was studied, and its adsorption mechanism was reasonably explained by the theoretical calculation.